A two-level computational approach for the elasto-plastic analysis of framed structures with composite cross-sections. (1st February 2019) - Bilotta, A.; Garcea, G.
Abstract: A new computational strategy for the elasto-plastic analysis of framed structures is proposed. The approach is composed of two levels of analysis: the frame level, based on a 3D mixed beam element, and the cross-section level, described through the Generalized Eigenvectors approach whose formulation is here extended for the analysis of materials with elasto-plastic behaviour. The proposed method, suitable for analyzing single beams as well as assemblages, can tackle composite cross-sections by taking into account all the stress components of the 3D solution.